Experimental evidence for the potential of lycopene in the management of scopolamine induced amnesia. Issue 89 (27th September 2015) - Bala, Rajni; Khanna, Deepa; Mehan, Sidharth; Kalra, Sanjeev
<x xml:space="preserve">Abstract</x> Lycopene successfully reversed the scopolamine induced amnesia.